Noise Measurement on Raya Merr Street, Surabaya - Rifky, Silvia; Sara, Lola; Amanah, Aulialula Maliuna; Prihantono, Gigih; Rosyidiana, Riska Nur (International Journal of Psychosocial Rehabilitation, 2020)
Noise is an unwanted sound from a business or activity at a certain level and time that can cause disruption to human health and environmental comfort. The noise level isdivided into 4 zones, zone A with a range of 35-45 dB, zone B with a range of 45-55 dB, zone C with a range of 50-60 dB, and zone D with a range of 60-70 dB. The noise source is divided into 2, that is static such as a factory or machine, and dynamic like a vehicle. The impact thatcan be obtained by the listener can be noise adaptation, physiological disorders, psychological disorders, communication disorders and the influence of hearing function. Noise measurement can be done using sound level meter and hand counter. This research was carried out on Raya Merr Street, Surabaya with latitude 7°15’54.24"S and longitude 112°46’57.73"T. The study washeld for 10x4 minutes or 4 series with an interval of 10 seconds. From that we get 240 data andcan find the sound pressure level of 10% and 90% (SPL10 and SPL90) with the data taken is thelower bound data. SPL10 is 75.5 and SPL90 is 65.5. The calculation results a noise value is 75.5 dB. The number of vehicles on the highway affects the value of noise intensity with acorrelation value of 65.51% and inversely proportional. The more number of vehicles, the lower the value of noise intensity.